2016
DOI: 10.1186/s12864-016-3093-4
|View full text |Cite
|
Sign up to set email alerts
|

Impaired telomere maintenance in Alazami syndrome patients with LARP7 deficiency

Abstract: BackgroundLoss of function in genes required for telomere maintenance result in disorders known as telomeropathies, which are characterized by a pattern of symptoms including generalized and specific lymphocytopenias as well as very short telomere length and disease anticipation.MethodsBecause human LARP7 is the most likely ortholog of the Tetrahymena p65 protein, which is required for telomerase activity in that organism, we investigated the effects of LARP7 silencing in human cells as well as in two distinct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 26 publications
0
35
0
Order By: Relevance
“…We describe a male infant who, at 17 months of age, is the youngest patient diagnosed with Alazami syndrome to date. He is also the first reported patient with an intronic variant predicted to cause abnormal splicing, as the variants previously‐reported in the literature are frameshift variants resulting in a prematurely truncated protein (Alazami et al, ; Dateki et al, ; Hollink et al, ; Holohan et al, ; Imbert‐Bouteille et al, ; Ling & Sorrentino, ). His physical development appears consistent with previous reports of Alazami syndrome, with short stature and characteristic facial features noted in addition to other features particular to Alazami syndrome such as overlapping toes and rough skin over his feet.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…We describe a male infant who, at 17 months of age, is the youngest patient diagnosed with Alazami syndrome to date. He is also the first reported patient with an intronic variant predicted to cause abnormal splicing, as the variants previously‐reported in the literature are frameshift variants resulting in a prematurely truncated protein (Alazami et al, ; Dateki et al, ; Hollink et al, ; Holohan et al, ; Imbert‐Bouteille et al, ; Ling & Sorrentino, ). His physical development appears consistent with previous reports of Alazami syndrome, with short stature and characteristic facial features noted in addition to other features particular to Alazami syndrome such as overlapping toes and rough skin over his feet.…”
Section: Discussionmentioning
confidence: 94%
“…In fact, only one patient is reported to have meaningful speech (Hollink et al, ), though these details are not consistently provided, and the younger patients reported may have yet to develop additional language skills. These individuals also share a unique facial gestalt with the initial family described and are all reported to have pathogenic protein‐truncating variants in LARP7 (Dateki et al, ; Hollink et al, ; Holohan et al, ; Imbert‐Bouteille et al, ; Ling & Sorrentino, ). The age at diagnosis ranges from 2 to 26 years of age and many families are reported to be consanguineous (Dateki et al, ; Hollink et al, ; Holohan et al, ; Imbert‐Bouteille et al, ; Ling & Sorrentino, ).…”
Section: Introductionmentioning
confidence: 97%
“…Notably, two human La family members, LARP3 and LARP7, have also been implicated in telomere maintenance. LARP7 has been reported to affect alternative splicing of Tert 38 , whereas LARP3 was found to associate with telomerase RNA 39 . Whether either of these proteins functions in a similar manner to p65 and Pof8 to promote telomerase assembly and activity remains to be tested.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently reported that knock down of LARP7 reduces telomerase activity in HeLa cells, and that Alazami syndrome patients carrying frame-shift mutations in LARP7 show a premature telomere shortening phenotype 61 . Such findings, along with our current report, might thus suggest that the LARP7 family proteins share a conserved role as an RNA chaperon in the assembly of an active telomerase complex.…”
Section: Discussionmentioning
confidence: 99%